Artesunate ameliorates high glucose-induced rat glomerular mesangial cell injury by suppressing the TLR4/NF-κB/NLRP3 inflammasome pathway. (25th September 2018) - Sun, Zhiqiang; Ma, Yali; Chen, Fang; Wang, Shiying; Chen, Baoping; Shi, Jun
Abstract: Inflammatory response is important for the development and progression of diabetic nephropathy (DN). Artesunate (ART), an antimalarial drug, possesses anti-inflammatory effect and exhibits protective effect on chronic kidney diseases. However, the effect of ART on DN is unknown. The aim of the present study was to evaluate the effect and the molecular mechanism of ART on DN in an in vitro model. The rat mesangial cell line, HBZY-1, was induced by high glucose (HG; 30 mMd -glucose) in the presence or absence of ART (15 and 30 μg/ml) and incubated for 24 h. We found that HG induced the proliferation of HBZY-1 cells, while treatment with ART inhibited the cell proliferation. Treatment with ART inhibited HG-induced inflammatory cytokines production and expression of extracellular matrix (ECM). Besides, HG induced reactive oxygen species (ROS) and malondialdehyde (MDA) levels, and inhibited the superoxide dismutase (SOD) activity of HBZY-1 cells, and the effects were attenuated by ART treatment. ART decreased HG-induced the expression levels of toll-like receptor 4 (TLR4), myeloid differentiation primary response gene 88 (MyD88), nuclear factor κB (NF-κB) p-p65, and nod-like receptor protein 3 (NLRP3). Inhibition of the TLR4/NF-κB pathway suppressed NLRP3 inflammasome in HBZY-1 cells. In conclusion, ART exhibited protective effect on HG-induced HBZY-1 cells by inhibiting the inflammatory response, oxidative stress and ECM accumulation. The TLR4/NF-κB/NLRP3 inflammasome pathway was involved in the protective effect of ART. The results suggested that ART might be a potential therapy agent for the DN treatment. Highlights: ART inhibited HG-induced proliferation of HBZY-1 cells. ART suppressed HG-induced inflammatory responses and oxidative stress. ART decreased the expression of extracellular matrix. ART inhibited TLR4/MyD88, NF-κB, and NLRP3 inflammasome pathways.